Annealing Effects on the Magnetoresistance Characteristics- of Sputtered FeNi-Cr Granular Magnetic Thin Films - Khoo, Suat Phin (1999)
The effect of the magnetic field and annealings on the magnetoresistance (MR.) of two series of FeNi-Cr granular magnetic thin films deposited by radio frequency magnetron sputtering system in vacuum on a glass substrate is discussed. The first series consist of (FeNi)₄₀Cr₆₀, (FeNi)₄₂Cr₅₈ (FeNi)₅₂Cr₄₈, (FeNi)₄₅Cr₅₅ and (FeNi)₅₇Cr₄₃ whereas the second series consist of FeNi-Cr granular magnetic thin films prepared at various radio frequency power (40W, SOW and 60W). The first series of samples were annealed at 400°C and 450°C for one hour. These films were annealed again at 390°C for two hours to obtain larger MR values. The films of the second series of the samples were annealed at 400°C only. The structure, microstructure and percentage of composition of the films were characterized by using x-ray diffraction (XRD), Scanning Electron Microscopy (SEM), Energy Dispersive Analysis (EDAX) while the MR of the samples under the influence of the magnetic field was studied by a standard four point probe technique.The structure of all the samples has been characterized by x-ray diffraction. The as-deposited and first annealed samples appear to be metastable where the halo pattern is prominent in all the graphs. After the second annealing, some prominent peaks are observed for certain samples. For the samples that have undergone two stages of annealings, after two annealings at 450°C for 1 hour and at 390°C for 2 hours, the peak of Ni [200] shifted to Ni [111] and Fe [110] at higher concentration of FeNi, resulting in further increase of MR. However the MR does not saturate at 1 Tesla, the maximum field available in the laboratory, for all samples. When the FeNi concentration is increased, the MR is also increased. The maximum of MR, -0.63%, has been observed in the film with 57% FeNi after two annealings at 450°C for 1 hour and at 390°C for 2 hours. The magnitude of MR is affected by the size and density of the magnetic entities which can be controlled by varying the composition and the preparation conditions. For application such as for the MR heads, a large MR ratio of about 2% due to a small applied field is desirable.